Targeting the estrogen pathway for the treatment and prevention of lung cancer - Burns, Timothy F (Lung Cancer Manag, 2014)
The estrogen signaling pathway is involved in the biology of non-small-cell lung cancer and represents a novel therapeutic target for lung cancer. This is supported by epidemiological evidence, preclinical studies and recent data from clinical trials. Antiestrogens and inhibitors of estrogen synthesis have been shown to inhibit lung tumor growth as well as prevent lung tumorigenesis in preclinical models both in vitro and in vivo. Two clinical trials testing the effectiveness of hormonal strategies in advanced non-small-cell lung cancer have recently been completed with promising results. Future work in this field should focus on identification of patients that would benefit from hormone modulators so that they can be used earlier in the course of disease or for chemoprevention.